Kebijakan Perizinan Berusaha di Indonesia dan Kepastian Hukum bagi Investor Pasca Putusan Inkonstitusional Bersyarat UU Cipta Kerja - Olivia Sabrina Br Manik (UNES Law Review, 2023)
The development and progress of investment activities is one of the things that has a very large role for the movement of the national economy. In order to maintain national economic stability, the government opens opportunities for investors with various facilities provided by Law Number 11 of 2020 concerning Job Creation (“Job Creation Law”). However, it is known the Job Creation Law was declared conditionally unconstitutional by the Constitutional Court Decision Number 91/PUU-XVIII/2020. Clarity is urgently needed regarding all regulations related to investment in order to realize the main objectives of the investment activity itself and to avoid all difficulties related to licensing bureaucracy. This normative research seeks to describe the business licensing policies after the Job Creation Law, the government's attitude towards the formal test decisions of the Job Creation Law, especially legal certainty for investors after the unconstitutional conditions of the Job Creation Law. Based on the research results, it is known that in order to guarantee legal certainty, investors should be able to continue carrying out their business activities on the basis of the Job Creation Law and its implementing regulations.